2008
DOI: 10.1002/jps.21102
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylserine Containing Liposomes Reduce Immunogenicity of Recombinant Human Factor VIII (rFVIII) in a Murine Model of Hemophilia A**Karthik Ramani and Razvan D. Miclea contributed equally to the manuscript.

Abstract: Factor VIII (FVIII) is a multidomain protein that is deficient in hemophilia A, a clinically important bleeding disorder. Replacement therapy using recombinant human FVIII (rFVIII) is the main therapy. However, approximately 15-30% of patients develop inhibitory antibodies that neutralize rFVIII activity. Antibodies to epitopes in C2 domain, which is involved in FVIII binding to phospholipids, are highly prevalent. Here, we investigated the effect of phosphatidylserine (PS)-containing liposomes, which bind to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

7
2

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 54 publications
(65 reference statements)
2
53
0
Order By: Relevance
“…Therefore, it is important to investigate the role of macromolecular interactions on catabolism and immunogenicity of FVIII. Our previous results showed that FVIII-PS complex reduced inhibitor development (27,28), but molecular details of catabolism of FVIII in vivo could not be clearly understood due to rapid uptake of PS by reticuloendothelial system (RES) (29,30). Here, we have replaced PS with another anionic phospholipid, PI, which resists RES uptake (31), and investigated its effect on the immunogenicity and catabolism of FVIII.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to investigate the role of macromolecular interactions on catabolism and immunogenicity of FVIII. Our previous results showed that FVIII-PS complex reduced inhibitor development (27,28), but molecular details of catabolism of FVIII in vivo could not be clearly understood due to rapid uptake of PS by reticuloendothelial system (RES) (29,30). Here, we have replaced PS with another anionic phospholipid, PI, which resists RES uptake (31), and investigated its effect on the immunogenicity and catabolism of FVIII.…”
Section: Introductionmentioning
confidence: 99%
“…administration, believed to result from rapid uptake by the reticuloendothelial system (RES) (25). Grafting liposomes with polyethylene glycol (PEG) has been shown to prolong liposome circulation in vivo (26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies showed that FVIII complexed with phosphatidylserine (PS) significantly reduced the development of antibody response against FVIII in HA mice (2,3). The studies aimed at understanding the mechanism of this reduction showed that FVIII-PS down-regulated the expression of CD40 upon exposure to bone marrow-derived dendritic cells (DC) (4).…”
mentioning
confidence: 99%